PUZZLE ELEKTRONIK MONTESSORI SAND BOARD LETTER(SBL) UNTUK EDUKASI SUKU KATA BAHASA INDONESIA PADA ANAK USIA DINI - Ihsan, Indah Purwitasari; Sakir, Muh; Yusuf, Farida (Universitas Halu Oleo, 2021)
Montessori is a learning method to stimulate children to reach their potential in all fields. In the field of reading literacy, one of the initial stages is how to stimulate initial reading skills, starting with introducing letters using the syllable learning method. The stimulation process must be in a fun and non-boring way of playing exploration so that children will not feel that they are learning, especially in the current state of the COVID-19 pandemic, where the learning process becomes boring for children because it has to be done at home. just. The purpose of this study is to create a learning technology in the form of an electronic Montessori Sand Board Letter (SBL) Puzzle for Indonesian syllables that can help stimulate early childhood according to the Montessori principle in recognizing syllables. The system development method uses the System Development Life-Cycle (SDLC) method. Based on the results of functional testing using the black box method, it is stated that the entire functional system is 100% functioning according to the system design. The results of testing and validation by Montessori practitioners state that the system has been made according to Montessori rules. Based on the results of usage observations, the Montessori Sand Board Letter (SBL) electronic puzzle for 85% Indonesian syllables can stimulate children's ability to recognize Indonesian syllables